2009
DOI: 10.1088/0004-637x/698/1/83
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Group Galaxies in Cnoc1 Clusters

Abstract: Using wide-field BV R c I imaging for a sample of 16 intermediate redshift (0.17 < z < 0.55) galaxy clusters from the Canadian Network for Observational Cosmology (CNOC1) Survey, we investigate the dependence of cluster galaxy populations and their evolution on environment. Galaxy photometric redshifts are estimated using an empirical photometric redshift technique and galaxy groups are identified using a modified friends-of-friends algorithm in photometric redshift space. We utilize the red galaxy fraction (f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 78 publications
5
32
0
Order By: Relevance
“…This method has been widely used to compute the luminosity function, e.g., Barkhouse et al (2007), and has been demonstrated numerically to be able to accurately recover the underlying luminosity function selected in three dimensions (Valotto et al 2001). We adopt the method to explore galaxy properties for photometric redshift samples, similar to the approach used in Loh et al (2008) and Li et al (2009). We stack galaxies around group centers within a redshift slice for which the redshift difference between galaxy and group has to be smaller than the photo-z accuracy, i.e., z z ) are galaxy redshift, group redshift, and photo-z accuracy, respectively.…”
Section: Background Subtractionmentioning
confidence: 99%
“…This method has been widely used to compute the luminosity function, e.g., Barkhouse et al (2007), and has been demonstrated numerically to be able to accurately recover the underlying luminosity function selected in three dimensions (Valotto et al 2001). We adopt the method to explore galaxy properties for photometric redshift samples, similar to the approach used in Loh et al (2008) and Li et al (2009). We stack galaxies around group centers within a redshift slice for which the redshift difference between galaxy and group has to be smaller than the photo-z accuracy, i.e., z z ) are galaxy redshift, group redshift, and photo-z accuracy, respectively.…”
Section: Background Subtractionmentioning
confidence: 99%
“…In a complementary analysis, Li, Yee & Ellingson (2009) observed that the fraction of blue galaxies increases faster with redshift in groups associated with Canadian Network for Observational Cosmology (CNOC1) clusters (Yee, Ellingson & Carlberg 1996) than in the clusters themselves. Finally, Tanaka et al (2007, 2009) have shown evidence of newly formed red galaxies with residual star formation in the large‐scale structure around clusters, indicating that these systems may be very effective in transforming galaxies over cosmic time.…”
Section: Introductionmentioning
confidence: 99%
“…The currently favoured explanation for these observed trends is that infalling field galaxies are processed physically as they travel from the field, through the cluster outskirts and virialize in the central cluster region (Berrier et al 2009). However, the extent to which cluster galaxies were ‘pre‐processed’ by physical effects occurring during an earlier residence in a galaxy group 1 remains contested (Li, Yee & Ellingson 2009). Numerous physical processes have been suggested as the agents of this apparent transformation of galaxy populations.…”
Section: Introductionmentioning
confidence: 99%